TINJAUAN YURIDIS KEPEMILIKAN TANAH MELALUI JUAL BELI YANG DI KLAIM PIHAK LAIN (STUDI PUTUSAN PENGADILAN NEGERI CIKARANG NOMOR 28/Pdt/2019/PN.Ckr) - amalya valensy; Endang Pandamdari (Jurnal Hukum Adigama, 2021)
Holders of land titles have the right to use the land. Transactions and transfers of land rights in Indonesia at this time need to be carried out before the PPAT so that the transfer of rights can be registered at the land office as enacted by Government Regulation No. 24 of 1997 concerning Land Registration, so that the transfer of land rights can be carried out, the sale and purchase of land carried out by the parties must be carried out before the PPAT with the aim of avoiding legal problems. Based on the contents in this thesis, there is a problem, namely how land ownership through buying and selling claims by other parties. Furthermore, the research method used is literature study, the approach method used by the author is the statutory approach. The legal awareness of a society must be supported by its legal culture. Negligence, whether intentional or not, will lead to uncertainty over the status of ownership of the land rights. Problems arise as a result of the recognition of land ownership by other people. According to land law in Indonesia, this sale and purchase transaction needs to be carried out before the PPAT. To resolve disputes between plaintiffs and defendants. Based on the evidence provided from the parties and the defendant, the judge decided that the deed used as evidence for the recognition of the defendant's land rights was declared null and void along with the derivative deed.